Advanced Care: Why We Need New Clinical Model. Issue 2 (1st June 2012) - Stuart, B
Abstract : Health care in the developed world is fractured across 3 distinct dimensions: space, time, and treatment. Poor handoffs between settings fragment care in the spatial dimension. As illness advances, evolving personal choices are not tracked in real time, so care becomes disconnected from patient preference. Finally, "curative treatment" and "comfort care" have become mutually exclusive. Seriously ill patients undergo hospitalizations, procedures and tests that confer little benefit until they no longer respond. At this point they are declared "terminal, " "treatment" ceases, and they become eligible for hospice. Palliative care alone cannot heal these splits, because it is confined mainly to the hospital setting, and it suffers from the same stigma of dying that afflicts hospice. Advanced Care proposes a new clinical model that coordinates care across all settings, documents personal choice over the whole course of late-stage illness, and provides a customized mix of treatment and comfort care that gives seriously ill people a chance to stay at home, stable and safe, for as long as possible. Advanced Care is person-centered, not patient-centered. In fact, it allows people with serious illness to avoid becoming patients. Data from innovative programs show that's what most of them want. Significant cost savings are a fortunate but unintended byproduct. A standardized model and metrics, along with systematic evaluation through a multi-site national pilot, are needed to provide access to the growing number of people who would benefit from this approach.